2022
DOI: 10.3389/fimmu.2022.1026509
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tai chi intervention on NLRP3 and its related antiviral inflammatory factors in the serum of patients with pre-diabetes

Abstract: BackgroundNLRP3 inflammasome and its related antiviral inflammatory factors have been implicated in the pathogenesis of type 2 diabetes mellitus (T2DM) and insulin resistance, but its contribution to pre-diabetes remains poorly understood.ObjectiveTo investigate the effects and the potential mechanism of Tai Chi intervention on NLRP3 inflammasome and its related inflammatory factors in the serum of middle-aged and older people with pre-diabetes mellitus (PDM).Methods40 pre-diabetic subjects were divided into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In this study, we found that the protein expressions of NLRP3 inflammasome components in pre-diabetic patients were higher as compared to normal healthy subjects, implying that the pre-diabetic patients were also in the chronic inflammatory state. In line with our results, one latest research also showed that the blood glucose, insulin resistance, and NLRP3 inflammasome activity were higher in prediabetic patients than in normal control subjects (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that the protein expressions of NLRP3 inflammasome components in pre-diabetic patients were higher as compared to normal healthy subjects, implying that the pre-diabetic patients were also in the chronic inflammatory state. In line with our results, one latest research also showed that the blood glucose, insulin resistance, and NLRP3 inflammasome activity were higher in prediabetic patients than in normal control subjects (22).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, recent studies showed that appropriate exercise was able to inhibit the overactivation of NLRP3 inflammasome in human models of T2DM ( 11 ), healthy young students ( 18 ), elderly subjects ( 19 , 20 ), obese children ( 21 ). However, the evidence of beneficial effects of exercise intervention on inhibiting NLRP3 inflammasome activation in pre-diabetic human models is largely unknown ( 22 ). Moreover, in recent years, the traditional Chinese exercises including TaiChi, Yijinjing, Wuqinxi, Baduanjin, Liuzijue have been noted, whereas the research on Yijinjing is less.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FBG, HbA 1 C, FINs, and HOMA-IR were increased, and HDL-C, HOMA-β were lower in the serum of the T2DM group when compared with those in the PDM group, indicating that the development of diabetes may be closely related to glucose and lipid metabolism, and IR. The NLRP3 inflammasome is a multiprotein complex responsible for the activation of inflammatory responses and plays an important role in the development of innate immunity and inflammation-related diseases [5] [14]. Brown et al found that the mRNA and protein levels of NLRP3, ASC, and Caspase-1 were elevated in diabetic rats from the 4 th or 8 th week of diabetes [15].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex pathogenesis of diabetes, it is characterized that chronic inflammation and insulin resistance (IR) are pivotal factors for the occurrence and development of diabetes [3]. The roles of inflammasome and its related factors in diabetes and IR have attracted much attention, and have become important targets for the prevention and treatment of metabolic diseases [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation